1992
DOI: 10.1007/bf00170594
|View full text |Cite
|
Sign up to set email alerts
|

Intra-colonial foraging specialism by honey bees (Apis mellifera) (Hymenoptera:Apidae)

Abstract: Colonies of honey bees with two identifiable subfamilies were established. Returning foragers were captured and killed at two different sampling times. The mean volume and per cent soluble solids of crop contents were determined for each subfamily, as was the mean weight of the pollen pellets. No significant differences in nectar volume or concentration were detected between subfamilies within colonies. However, in a few colonies, significant subfamily by sampling-time interactions were present, suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…Behavioral polymorphisms among subfamilies have been found for a wide variety of critical tasks [14,17,19,34,41,45,46,48,49,62,70,71,74,75]. It has been often argued that this variation is adaptive and that task specialization allows individual bees to focus on particular tasks and become expert in them [8,47,75].…”
Section: The Subset Of Hypotheses Relating To Worker Diversitymentioning
confidence: 99%
“…Behavioral polymorphisms among subfamilies have been found for a wide variety of critical tasks [14,17,19,34,41,45,46,48,49,62,70,71,74,75]. It has been often argued that this variation is adaptive and that task specialization allows individual bees to focus on particular tasks and become expert in them [8,47,75].…”
Section: The Subset Of Hypotheses Relating To Worker Diversitymentioning
confidence: 99%
“…It has been shown that polyandry, and the resultant intracolony genetic diversity of the worker force, confers numerous benefits to a colony (reviewed by Palmer and Oldroyd, 2000). First, genetic diversity may increase the behavioral diversity of the worker force (Fuchs and Schade, 1994;Oldroyd et al, 1994;Moritz and Fuchs, 1998;Mattila and Seeley, 2007), such as enabling colonies to exploit different foraging environments more efficiently (Lobo and Kerr, 1993;Mattila et al, 2008) or providing a buffer against fluctuations in the environment (Oldroyd et al, 1992;Page et al, 1995;Jones et al, 2004). Second, genetic diversity may reduce the impacts of diploid male production as a consequence of the single-locus sex determination system (Page, 1980;Ratnieks, 1990;Crozier and Pamilo, 1996;Tarpy and Page, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that bees possess the ability to finely adjust several components of their foraging behavior according to the quality of the nectar source (Núñez, 1970(Núñez, , 1982Seeley et al, 1991;Seeley, 1995). Several works pointed out the effect of the nectar flow rate and concentration, nutritional state of the colony, genetic constitution and other variables on the foraging behavior of individual bees (Núñez, 1970(Núñez, , 1982Seeley, 1995;Seeley et al, 1991;Oldroyd et al, 1992). However, little is known about how bee foraging behavior is affected by 302 P.C.…”
Section: Introductionmentioning
confidence: 99%